Is patient activation a mediator of the effect of a health promoting intervention in adults at high risk of type 2 diabetes? A longitudinal path model analysis within a randomised trial - Morten Frydenberg; Helle Terkildsen Maindal; Adam Fletcher; Lise Juul (BMC, 2022)
Abstract Background Exploring mediators of preventive intervention effects has important implications for the planning of complex interventions. Our aim was to assess the extent to which knowledge, skills and confidence to manage health, here measured as "patient activation", was a mediator of the effect of the intervention "Live your life without diabetes" on weight, waist circumference and systolic blood pressure at 12 months follow-up in adults at high risk of type 2 diabetes. Methods Autoregressive path models with three time points of measurement, and contemporaneous and constant b paths were used in a randomised controlled trial (RCT). The RCT took place in a Danish municipal healthcare center and included 127 individuals aged 28 to 70 years with fasting plasma glucose: 6.1-6.9 mmol/l and/or glycated haemoglobin (HbA1c): 42.0-47.9 mmol/mol. Participants were randomised to routine care (n = 64), or intervention (n = 63). The intervention group received an empirical and theory-based intervention delivered over four two-h group sessions during five weeks, and two further sessions after one and six months. The outcomes were weight, waist circumference and systolic blood pressure, and the mediator was patient activation, measured by the self-reported Patient Activation Measure (PAM). Data for the present study was derived from questionnaires and clinical measures from baseline, three- and 12-months follow-up. Results Mediated effects via PAM on: weight: − 0.09 kg (95% CI − 0.38 to 0.20) out of the total effect − 1.09 kg (95% CI − 3.05 to 0.87); waist circumference: − 0.04 cm (95% CI − 0.36 to 0.28) out of the total effect − 1.86 cm (95% CI − 4.10 to 0.39); and systolic blood pressure: − 0.31 mmHg (− 1.10 to 0.49) out of the total effect − 2.73 mmHg (95% CI − 6.34 to 0.87). Conclusion We found no mediating effects of patient activation as a single variable of the intervention "Live your life without diabetes" on weight, waist circumference and systolic blood pressure at 12 months follow-up in adults at high risk of type 2 diabetes. Our study demonstrates an analytic approach for estimating mediating effects in complex interventions that comply with the criteria on temporal ordered data. Future studies should include possible interacting variables.